The Effects of Biochar and Compost on Different Cultivars of Shallots (Allium ascalonicum L.) Growth and Nutrient Uptake in Sandy Soil Under Saline Water - Rahayu Rahayu; Jauhari Syamsiyah; Vita Ratri Cahyani; Siti Kharisma Fauziah (Universitas Sebelas Maret, 2019)
High salinity irrigation will cause nutrient uptake and shallot growth to deplete due to its sensitivity to salinity. This research aimed to investigate the effect of biochar and compost on shallot growth and nutrient uptake in sandy soil like Entisol when irrigated using salty water. This research carried out some pot experiments and put on the field using a completely randomized design. The first factor was based on the amendment with control of 20 tons ha-1 of Biochar, 10 tons ha-1 of compost, and a mixture of 10 tons ha-1 biochar and 5 tons ha-1 of compost; the second factor was composed of 3 shallot cultivars (Brebes, Pemalang, and Purbalingga). Each pot was filled with 15 kg of soil; the pot 30 cm in diameter, incubated with saline water and irrigated by 2 dS m-1. The results show that irrigation with ground saline water causes Entisol to increase exchangable Na, Ece and SAR, decrease exchangeable Ca and Mg. The application of all treatments decreased SAR. The application of compost significantly increased N and K uptake but made soil pH, EC, and SAR to decrease while fresh weight and dry weight of bulb in Brebes cultivars increased. The combination of biochar with 5 tons ha-1 of compost produced the highest yield on plant height and number of tuber in Pemalang cultivars and had the largest tuber diameter in Purbalingga cultivars. There is an interaction between amendment and cultivar on plant height, fresh weight of tuber (P<0.01), dry weight of tuber (P<0.01).